The Effectiveness of Multimodal Treatment Strategies (Antibiotics, Anti-inflammatory Drugs, and Lifestyle Modifications) in Reducing Prostatitis Symptoms: A Systematic Review - Ilham Saptia Nugraha; John M. Sangkai (The International Journal of Medical Science and Health Research, 2025)
Introduction: Prostatitis, particularly Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS), is a prevalent and debilitating condition with a profound negative impact on patients' quality of life. Its complex, multifactorial pathophysiology, involving infection, inflammation, and neuromuscular dysfunction, renders traditional monotherapy largely ineffective. This systematic review synthesizes the evidence on the effectiveness of multimodal treatment strategies to establish an evidence-based standard of care. Methods: Following PRISMA guidelines, a systematic search of PubMed, Semantic Scholar, Springer, Google Scholar, and Wiley Online Library was conducted. The review included randomized controlled trials and prospective cohort studies evaluating multimodal therapies (combinations of antibiotics, anti-inflammatories, and/or lifestyle modifications) in adult men with prostatitis. The primary outcome was the mean change in the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) score. Results: The analysis of six selected studies demonstrated that multimodal therapies lead to statistically and clinically significant reductions in prostatitis symptoms. Pharmacological combinations of alpha-blockers, anti-inflammatories, and antibiotics resulted in substantial decreases in NIH-CPSI scores. The integration of structured lifestyle modifications, such as diet and aerobic exercise, further enhanced symptom control. Phenotype-directed therapy using the UPOINT system, which tailors treatment to individual symptom domains, proved most effective, with over 75% of patients achieving a clinically significant response. Discussion: The superiority of a multimodal approach stems from its synergistic ability to simultaneously target the distinct pathophysiological domains of prostatitis. The UPOINT framework signifies a paradigm shift towards personalized medicine, enabling clinicians to move beyond a "one-size-fits-all" strategy to a tailored, effective treatment plan. These findings strongly align with and provide a quantitative evidence base for current AUA and EAU clinical practice guidelines that advocate for multimodal management. Conclusion: This review consolidates robust evidence that multimodal treatment, particularly when guided by clinical phenotyping like the UPOINT system, is unequivocally superior to monotherapy. It represents the gold-standard, evidence-based paradigm for managing prostatitis, offering patients the greatest potential for meaningful symptom improvement.